Effects of Colchicine and Oryzalin on Callus and Adventitious Shoot Formation of Euphorbia pulchurrima 'Winter Rose' - Pickens, K.A; Cheng, Z.M; Kania, S.A (HortScience, 2006)
The mitotic inhibitors, colchicine and oryzalin, were evaluated for their effects on callus, adventitious shoot formation, and tetraploid induction of Euphorbia pulchurrima 'Winter Rose'. In vitro grown leaf sections were placed on various media supplemented with either colchicine or oryzalin at various concentrations for 1 to 4 days. Colchicine was less damaging to leaf tissues than oryzalin. On various colchicine-containing media, prolific calluses were produced and adventitious shoot formation was observed. Regenerated shoots were found to be diploid as determined by flow cytometry. On media supplemented with oryzalin (28.9 micromolar to 144 micromolar), leaf tissues produced callus but failed to form adventitious shoots. Samples of calluses produced on oryzalin-containing media were subject to analysis using flow cytometry and were found to be diploid. These results suggest that the colchicine is less toxic on poinsettia tissues and shoot induction than oryzalin. Additional experiments are needed to establish a protocol for in vitro induction of poinsettia tetraploid with colchicine and oryzalin.